The Causes of Prolonged ED Stays for Female Patients with Acute Abdominal Pain - Emine Ayça Şahin; Nuri Havan; Cem Ayan; Hüseyin Yüzlü; Umut Özdamarlar; Doğaç Niyazi Özüçelik (Global Emergency and Critical Care)
Objective: Female emergency department (ED) patients with abdominal pain require consultation and investigation for accurate diagnosis, thus prolonging their stay. Materials and Methods: This study employed a retrospective design and focused on female patients who sought medical attention at an ED between April and September 2015. The study included patients who were referred to general surgery and/or obstetrics and gynecology clinics for consultation. Other variables included the length of stay (LOS), duration of consultations, recommendations provided in the consultation notes, and laboratory and imaging results. Results: The data of 1,146 patients were analyzed over a 6-month period. Upon analysis of their hospitalization and discharge status, it was concluded that there was no statistically significant disparity in terms of LOS in the ED (p=0.611). Patients who underwent computed tomography scans, had negative beta human chorionic gonadotropin results, or sought general surgeon consultation had longer stays in the ED. Conclusion: The sequential administration of examinations and consultations prolonged the ED stays of female abdominal pain patients. Thus, a standardized protocol for female abdominal pain patients is widely believed to be necessary.